Deregulation, financial deepening and savings performance in Zambia: 1978-2006 - Simwanza, Harriet (School of Economics, 2024)
This paper attempts to review the impact of financial reforms largely undertaken in the early 1990s on the financial sector of Zambia. In particular, it investigates the influence of the reforms on the depth of the financial sector. This analysis is made by means of simple monetary and financial ratios. The paper further seeks to explore the behavour of financial savings in relation to real GDP, financial deepening, inflation, and real interest rate using an error correction model over two sample periods, with one period representing the pre-liberalisation period and the other representing the post-liberalisation period. The paper finds that there has not been any significant growth in the depth of the financial sector. With regard to the behaviour of financial savings, the empirical results show that financial savings respond more positively to an increase in financial depth and an increase in real deposit rate for the post-liberalisation period.